Penerapan Konsep Recreational space pada Perancangan Beach Resort di Pulau Pisang Gadang Kota Padang - Hardi, Resty Aprila (Universitas Pelita Bangsa, 2024)
Pisang Gadang Island is one of the tourist attractions included in the Air Manis Beach Tourist Area in Padang City. According to the Padang City Tourism Office, Air Manis Beach is one of the tourist areas that will be the focus of government improvement in the Gunung Padang Integrated Tourism Destination Improvement Work Programme. With a budget of Rp 15 billion from the state budget (APBN), the Padang city government started the revitalisation of Air Manis Beach in early August last year. This beach has considerable tourism potential, as evidenced by the large number of visitors during holidays and vacations, which is increasing every year. However, the increase in the number of tourists has not been matched by an increase in the number of holiday homes. Based on the need for recreational accommodation in the area to support the natural potential of Pisang Gadang Island, the application of the Recreational space concept to the design of beach resorts with an emphasis on creating accommodation that is enjoyable and makes people feel comfortable. The method used in the design of the beach resort, more emphasis on what problems exist in the design object area, namely in the area of Pisang Island. In addition, there are some literature that can be used and become a standard in the design of beach resort. So that it can produce a beach resort design that is not only able to meet the accommodation needs in South Padang District, but also able to provide recreational facilities with a recreational space approach.